Discovery of a non-cationic cell penetrating peptide derived from membrane-interacting human proteins and its potential as a protein delivery carrier - Young Kim, Hyo; Young Yum, Soo; Jang, Goo; Ahn, Dae-Ro (Scientific reports, 2015)
Cell penetrating peptides (CPPs) are peptides that can be translocated into cells and used as a carrier platform for the intracellular uptake of cargo molecules. Subject to the source of CPP sequences and their positively charged nature, the cytotoxicity and immunogenicity of conventional CPPs needs to be optimized to expand their utility for biomedical applications. In addition to these safety issues, the stability of CPPs needs to be addressed since their positively charged residues are prone to interact with the biological milieu. As an effort to overcome these limitations of the current CPP technology, we isolated CPP candidate sequences and synthesized peptides from twelve isoforms of annexin, a family of membrane-interacting human proteins. The candidate screen returned a CPP rich in hydrophobic residues that showed more efficient cellular uptake than TAT-CPP. We then investigated the uptake mechanism, subcellular localization and biophysical properties of the newly found CPP, verifying low cytotoxicity, long-term serum stability and non-immunogenicity. Finally, model proteins conjugated to this peptide were successfully delivered into mammalian cells both in vitro and in vivo , indicating a potential use of the peptide as a carrier for the delivery of macromolecular cargos.